1997
DOI: 10.1121/1.418175
|View full text |Cite
|
Sign up to set email alerts
|

Masking by modulated and unmodulated noise: Effects of bandwidth, modulation rate, signal frequency, and masker level

Abstract: The threshold for a sinusoidal signal masked by a band of noise is often times lower when the masking noise is modulated than when it is unmodulated. The difference in masked thresholds is referred to as the modulated-unmodulated difference, or MUD. These present experiments examined the effects of masker bandwidth, masker rate, and masker level on the MUD at several different signal frequencies. The MUD generally increased with increasing masker bandwidth; for masker bandwidths wider than a critical band (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…If true, this could explain differences in the size of within- and across-channel CMR. Within-channel configurations produce behavioral CMR several times larger than across-channel CMR (Carlyon et al, 1989; Bacon et al, 1997; Verhey et al, 2003). Likewise, Nelken et al (1999) observed locking suppression (decreased noise representation) at very low SNRs.…”
Section: Discussionmentioning
confidence: 94%
“…If true, this could explain differences in the size of within- and across-channel CMR. Within-channel configurations produce behavioral CMR several times larger than across-channel CMR (Carlyon et al, 1989; Bacon et al, 1997; Verhey et al, 2003). Likewise, Nelken et al (1999) observed locking suppression (decreased noise representation) at very low SNRs.…”
Section: Discussionmentioning
confidence: 94%
“…A number of experimental conditions have been investigated in previous CMR studies, which have not been considered directly in the present study. These studies investigated in much more detail effects of signal frequency ͑e.g., Moore, 1987͒, masker spectral width ͑Haggard et al, 1990;masker spectral level ͑Moore andShailer, 1991;Bacon et al, 1997;Cohen, 1991;Hall, 1986;McFadden, 1986͒, the influence of the envelope statistic of the masker modulator ͑e.g., Eddins and Wright, 1994;Grose and Hall, 1989;Hicks and Bacon, 1995͒, the effect of modulation frequency and modulation depth ͑Car-lyon and Stubbs, 1989;Hall et al, 1996;Lee and Bacon, 1997;Bacon et al, 1997;Verhey et al, 1999;Eddins, 2001͒, effects of flanking band number and flanking band level ͑e.g., Hatch et al, 1995;Schooneveldt and Moore, 1987͒ and other effects. The current version of the model does not include a nonlinear peripheral filtering stage and therefore cannot account for level-dependent cochlear compression and effects associated with it such as level-dependent frequency tuning and suppression.…”
Section: Limitations Of the Current Modeling Approachmentioning
confidence: 99%
“…One potential explanation for this result is that the target is at a higher sensation level and may be more detectable in the presence of modulated distractors than among unmodulated distractors, given that a pure tone is more detectable in a modulated masker than in an unmodulated masker ͑the socalled modulated-unmodulated difference, or MUD; Carlyon et al, 1989;Bacon et al, 1997͒. Perhaps increasing the detectability of the target ͑and so increasing its sensation level͒ in the presence of distractors makes its ITD more separable and reduces thresholds.…”
Section: Experiments 4: Effect Of Sensation Level On Target Lateralmentioning
confidence: 99%